Rubber sealing strip and preparation method thereof
Through the use of modified montmorillonite and modified carbon black, the problems of aging and degradation of sealing properties of traditional rubber seal strips are solved, higher performance and lower filler usage are achieved, and production efficiency and product quality are improved.
Patent Information
- Application Number
- CN202510222782.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional rubber seal strips are prone to aging and deforming during use, resulting in a decrease in sealing performance. The excessive addition of filler will increase production cost and processing difficulty, and reduce sealing performance and service life.
Modified montmorillonite and modified carbon black are used to improve its compatibility and dispersion through hydrolysis and condensation reactions of oleic acid intercalation and ethyl orthosilicate, reduce the use of fillers, and improve the uniformity and binding force of fillers through ball milling and ultrasonic dispersion.
The performance of rubber seal strips is significantly improved, including enhanced tensile strength, heat resistance and aging resistance, improved processing performance and production efficiency, and reduced defective rate and cost.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sealing strip production, and in particular to a rubber sealing strip and a preparation method thereof. Background Art
[0002] Rubber sealing strips are widely used in automobiles, construction, home appliances and other fields. Their main function is to prevent the penetration of gas, liquid and dust. Traditional rubber sealing strips are prone to aging and deformation during use, resulting in reduced sealing performance. The addition of fillers such as carbon black can improve the tensile strength, tear strength and hardness, aging resistance, wear resistance and sealing performance of rubber sealing strips. However, excessive addition of fillers not only increases production costs, but also leads to poor processing performance of rubber, such as difficulty in mixing, reduced fluidity of rubber, and difficulty in obtaining uniform size and good surface quality during extrusion molding. Moreover, excessive fillers will destroy the molecular structure of rubber, reduce its elasticity and flexibility, make rubber sealing strips prone to brittle cracking during use, and reduce sealing performance and service life. Summary of the invention
[0003] The first technical problem to be solved by the present invention is: to provide a rubber sealing strip in view of the deficiencies in the prior art, which reduces the amount of filler used and improves the performance of the rubber sealing strip.
[0004] To solve the above-mentioned first technical problem, the technical solution of the present invention is: A rubber sealing strip, the raw materials of which include base rubber, modified montmorillonite, modified carbon black, plasticizer, vulcanizer, antioxidant and other additives; The preparation method of modified montmorillonite is: Montmorillonite is added into deionized water and ultrasonically treated for 15-30 minutes to obtain a montmorillonite suspension; Dissolve oleic acid in an organic solvent, stir evenly to make the oleic acid completely dissolved, and obtain an oleic acid solution; Add the montmorillonite suspension to the oleic acid solution while stirring. After the reaction is completed, centrifuge the product, wash it repeatedly with ethanol or deionized water for more than 3 times, and then dry the washed product at 60-80°C to constant weight to obtain modified montmorillonite. The preparation method of modified carbon black is: Add carbon black to an ethanol-water mixed solution, and disperse by ultrasonic at 100-300W for 30-60min to obtain a carbon black dispersion; Add ammonia solution to the carbon black dispersion, adjust the pH value to 9-11, and then continue to add tetraethyl orthosilicate. After the addition is completed, place the reaction system in a constant temperature water bath, and react at a temperature of 40-60°C and a stirring speed of 300-600r / min for 2-6h; After the reaction is completed, the reaction solution is centrifuged at a speed of 4000-6000 r / min for 10-20 min, the supernatant is discarded, and then the precipitate is washed alternately with anhydrous ethanol and deionized water for 3-5 times; The washed precipitate is placed in an oven at 60-80°C and dried for 12-24 hours until constant weight is reached; The dried sample is placed in a high temperature furnace and calcined at 400-600°C for 2-4 hours to obtain modified carbon black.
[0005] Preferably, the base rubber is composed of EPDM rubber and silicone rubber in a mass ratio of 10:3-8.
[0006] Preferably, the added amount of the modified montmorillonite is 8-15% of the mass of the base rubber, and the added amount of the modified carbon black is 22-28% of the mass of the base rubber.
[0007] Preferably, the plasticizer is one of tributyl citrate and acetyl tributyl citrate or a mixture of the two, and the added amount is 8-12% of the mass of the base rubber.
[0008] Preferably, the vulcanizing agent is one or a mixture of di-tert-butyl diisopropylbenzene peroxide and diisopropylbenzene peroxide, and the added amount is 1.5-2.5% of the mass of the base rubber.
[0009] Preferably, the antioxidant is compounded by antioxidant 4010NA and antioxidant RD in a mass ratio of 1:1-2, and the total addition amount is 1-3% of the mass of the base rubber.
[0010] Preferably, other additives include zinc oxide, stearic acid and accelerator in a weight ratio of 3-5:1-2:0.5-2, and the total added amount is 5-8% of the mass of the base rubber, wherein the accelerator is a mixture of 2-mercaptobenzothiazole and N-cyclohexyl-2-benzothiazolesulfonamide, wherein the mass ratio of 2-mercaptobenzothiazole and N-cyclohexyl-2-benzothiazolesulfonamide is 1:1.5-2.
[0011] Preferably, the ratio of montmorillonite to deionized water in the montmorillonite suspension is 30-80 g / L; The weight ratio of oleic acid to organic solvent is 1:10-20, and the organic solvent is one of ethanol or toluene; The reaction temperature of montmorillonite and oleic acid is 50-80°C, and the reaction time is 2-6h.
[0012] Preferably, the particle size of carbon black is 20-50 nm; The carbon black was pretreated by drying in an oven at 100-120°C for 2-4h before being added to the ethanol-water mixed solution; The volume ratio of ethanol to water in the ethanol-water mixed solution is 3:1-5:1; The mass fraction of the ammonia solution is 25-28%wt; The mass ratio of ethyl orthosilicate to carbon black is 0.5:1-2:1, and the dropping speed of ethyl orthosilicate is 1-2 drops / second.
[0013] The second technical problem to be solved by the present invention is: in view of the deficiencies in the prior art, a method for preparing a rubber sealing strip is provided, which reduces the amount of filler used and improves the performance of the prepared rubber sealing strip.
[0014] To solve the above second technical problem, the technical solution of the present invention is: A method for preparing a rubber sealing strip comprises the following steps: Add the base rubber to the open mill, set the roller distance to 3-5mm, the roller temperature to 40-60℃ for plastication, and the time is 10-15min; Put modified montmorillonite, modified carbon black and grinding balls into a ball mill in a certain proportion, with a ball-to-material ratio of 5-10:1, set the speed of the ball mill to 200-500r / min, and the ball milling time to 4-10h. After the ball milling is completed, separate the grinding balls through a sieve and collect the blend; The plasticized base rubber is put into an internal mixer, the initial temperature of the internal mixer is set to 50-60°C, and then the blend of modified montmorillonite and modified carbon black, plasticizer, antioxidant and other additives are added in sequence, and mixed for 8-12 minutes, with the rotor speed of 40-60r / min to make the components fully mixed; Finally, add the vulcanizing agent and continue mixing for 3-5 minutes. Put the mixed rubber into the hopper of the extruder. The extruder temperature is controlled at 60-100℃ and the screw speed is 20-40r / min. The rubber is extruded into the required sealing strip shape through the extrusion die. The extruded sealing strip is vulcanized with hot air, the vulcanization temperature is controlled at 160-180℃, the vulcanization time is 10-20min, and the vulcanized sealing strip is cooled to room temperature through a cooling water tank, and the cooling water temperature is controlled at 10-20℃; The cooled sealing strip is cut to obtain a rubber sealing strip.
[0015] Due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. The present invention modifies montmorillonite by oleic acid intercalation, thereby increasing the interlamellar spacing, enhancing the compatibility with rubber molecules, and dispersing it more evenly in the rubber matrix, so that its reinforcing effect can be fully exerted at a lower dosage. A layer of silicon dioxide coating can be formed on the surface of carbon black through the hydrolysis and condensation reaction of ethyl orthosilicate. This coating can not only improve the surface properties of carbon black, but also enhance its compatibility with the matrix material. After carbon black pretreatment, ultrasonic dispersion and coating, the surface activity is improved, and the binding force with rubber molecules is enhanced. The effects of reinforcement and wear resistance that may have required more ordinary carbon black to achieve can now be achieved with less modified carbon black. Its performance has been significantly optimized, thereby reducing its usage in the production of rubber sealing strips, avoiding the increase in the Mooney viscosity of the rubber compound caused by the large amount of montmorillonite and carbon black used, and the deterioration of processing fluidity, which can improve the processing performance of the compound, such as easier extrusion and molding, improving production efficiency and product quality stability, and reducing the defective rate.
[0016] 2. The lamellar structure of oleic acid-modified montmorillonite and silica-modified carbon black can be interwoven to form a more complex and dense physical barrier network. Montmorillonite lamellar layers can fill the gaps between carbon black particles, and carbon black can support the montmorillonite lamellar layers, making the barrier layer more continuous and stable, and more effective in blocking oxygen and heat transfer. The two work together to improve the thermal stability of rubber. At high temperatures, the heat absorption effect of silica and the barrier effect of montmorillonite jointly reduce the thermal degradation rate of rubber, delay the combustion process, enhance the rubber's tolerance to fire, eliminate the need for separate addition of flame retardants, and reduce costs.
[0017] 3. The molecular structure of tributyl citrate and acetyl tributyl citrate contains multiple ester groups, which can form strong interactions with rubber molecules and the surface of modified montmorillonite. On the one hand, the plasticizer enhances the mobility of the rubber molecular chain segments, and on the other hand, the synergistic effect promotes the uniform dispersion of modified montmorillonite in the rubber, improves the flexibility, low temperature resistance and aging resistance of the rubber, and reduces the amount of modified montmorillonite added.
[0018] 4. Di-tert-butyl diisopropylbenzene peroxide and diisopropylbenzene peroxide decompose to produce free radicals when heated, which trigger cross-linking reactions between rubber molecular chains. When used in conjunction with modified montmorillonite, the free radicals produced by peroxide can attack the active sites on the surface of modified montmorillonite, forming chemical bonds between modified montmorillonite and rubber molecules, and enhancing the interfacial interaction between modified montmorillonite and rubber matrix. At the same time, peroxide-cured rubber has good heat resistance and aging resistance. Combined with the reinforcing effect of modified montmorillonite, it can significantly improve the performance of rubber in high temperature environments, while the large number of active groups on the surface of modified carbon black can capture the free radicals produced by rubber at high temperatures and inhibit the thermal oxidation degradation reaction of rubber. The chemical bonds formed between modified montmorillonite and rubber molecules and the barrier effect of its layered structure can also reduce the erosion of rubber by oxygen and other small molecules, delay the aging process of rubber, and improve the long-term stability of rubber in high temperature environments.
[0019] 5. The protective effect of 4010NA is more significant in the short term and can quickly play an anti-aging role; while antioxidant RD has a long-term effect and can continue to provide protection for rubber over time. The combination of the two allows the rubber sealing strip to maintain good performance during long-term use and extend its service life. In addition, when 4010NA and antioxidant RD play an anti-aging role in rubber, modified carbon black can be used as a carrier to make the antioxidant more evenly dispersed in the rubber matrix and improve the efficiency of the antioxidant. The modified montmorillonite has a layered structure and can play a physical barrier role in rubber. It can also improve the dispersibility of other additives. Under the action of modified montmorillonite, 4010NA and antioxidant RD can be more evenly dispersed in the rubber matrix, so as to fully play the anti-aging role. Under the synergistic effect, the interlayer of the modified montmorillonite can adsorb some antioxidant molecules and slowly release them during the aging process of rubber, realizing the long-term effect of the antioxidant.
[0020] 6. The dispersing effect of stearic acid can make oleic acid modified montmorillonite and silica modified carbon black better dispersed in the rubber matrix, avoiding the occurrence of agglomeration. The complex formed by zinc oxide and stearic acid can further promote the interaction between these modified fillers and rubber molecules, improve their dispersion stability in rubber, and the dispersing effect of stearic acid further reduces the usage of modified montmorillonite and modified carbon black.
[0021] 7.2-Mercaptobenzothiazole has a certain polarity and can quickly interact with the oleic acid groups on the surface of oleic acid-modified montmorillonite and the silica layer on the surface of silica-modified carbon black, enhancing their dispersion in the rubber matrix. This better dispersion can make the montmorillonite flakes and carbon black particles more evenly distributed in the rubber, thereby optimizing the physical properties of the rubber. As a late-effect accelerator, N-cyclohexyl-2-benzothiazole sulfonamide cooperates with 2-mercaptobenzothiazole to give oleic acid-modified montmorillonite and silica-modified carbon black enough time to be evenly dispersed in the rubber, allowing the modified filler to better combine with the rubber molecules to form a more complete cross-linking structure.
[0022] 8. Sulfonamide accelerators can enhance the interfacial interaction between modified montmorillonite and modified carbon black and rubber, improve the tensile strength, tensile stress and aging resistance of rubber, and give full play to the reinforcing effect of modified fillers. DETAILED DESCRIPTION
[0023] The present invention will be further described below in conjunction with the embodiments. Example 1
[0024] A method for preparing a rubber sealing strip comprises the following steps: Add the base rubber (EPDM and silicone rubber) to the open mill, set the roller distance to 3-5mm, the roller temperature to 40-60℃ for plastication for 10-15min; Put modified montmorillonite, modified carbon black and grinding balls into a ball mill in a certain proportion, with a ball-to-material ratio of 5-10:1, set the speed of the ball mill to 200-500r / min, and the ball milling time to 4-10h. After the ball milling is completed, separate the grinding balls through a sieve and collect the blend; The plasticized base rubber is put into an internal mixer, the initial temperature of the internal mixer is set to 50-60°C, and then the blend of modified montmorillonite and modified carbon black, plasticizer, antioxidant and other additives are added in sequence, and mixed for 8-12 minutes, with the rotor speed of 40-60r / min to make the components fully mixed; Finally, add the vulcanizing agent and continue mixing for 3-5 minutes. Put the mixed rubber into the hopper of the extruder. The extruder temperature is controlled at 60-100℃ and the screw speed is 20-40r / min. The rubber is extruded into the required sealing strip shape through the extrusion die. The extruded sealing strip is vulcanized with hot air, the vulcanization temperature is controlled at 160-180℃, the vulcanization time is 10-20min, and the vulcanized sealing strip is cooled to room temperature through a cooling water tank, and the cooling water temperature is controlled at 10-20℃; The cooled sealing strip is cut to obtain a rubber sealing strip. Example 2
[0025] The rubber sealing strip prepared according to the method of Example 1, wherein Base rubber: The mass ratio of EPDM rubber and silicone rubber is 10:3, totaling 100g.
[0026] Modified montmorillonite: The addition amount is 8% of the base rubber mass, i.e. 8g. According to the preparation method, 30g of montmorillonite is added to 1L of deionized water and ultrasonically treated for 15min, 10g of oleic acid is dissolved in 100g of ethanol, mixed and reacted, reacted at 50℃ for 2h, centrifuged, washed, and dried at 60℃ to constant weight.
[0027] Modified carbon black: The amount added is 22% of the mass of the base rubber, i.e. 22g. N330 carbon black with a particle size of 20nm was dried in an oven at 100℃ for 2h, added with a mixed solution of ethanol-water (volume ratio 3:1), ultrasonically dispersed at 100W for 30min, ammonia water was added dropwise to adjust the pH to 9, and tetraethyl orthosilicate was added dropwise at a mass ratio of 0.5:1, stirred at 40℃ and 300r / min for 2h, centrifuged, washed, dried at 60℃ for 12h, and calcined at 400℃ for 2h.
[0028] Plasticizer: tributyl citrate, the added amount is 8% of the base rubber mass, i.e. 8g.
[0029] Vulcanizing agent: diisopropyl ditert-butyl peroxide, the added amount is 1.5% of the base rubber mass, i.e. 1.5g.
[0030] Antioxidant: The mass ratio of antioxidant 4010NA and antioxidant RD is 1:1, and the total addition amount is 1% of the base rubber mass, i.e. 1g.
[0031] Other additives: The weight ratio of zinc oxide, stearic acid and accelerator is 3:1:0.5, and the total addition amount is 5% of the base rubber mass, i.e. 5g. The mass ratio of 2-mercaptobenzothiazole and N-cyclohexyl-2-benzothiazolesulfenamide in the accelerator is 1:1.5. Example 3
[0032] The rubber sealing strip prepared according to the method of Example 1, wherein Base rubber: The mass ratio of EPDM rubber and silicone rubber is 2:1, totaling 100g.
[0033] Modified montmorillonite: The addition amount is 10% of the base rubber mass, i.e. 10 g. 50 g of montmorillonite is added to 1 L of deionized water and ultrasonically treated for 20 min. 10 g of oleic acid is dissolved in 150 g of toluene, reacted at 60 ° C for 3 h, centrifuged, washed, and dried at 70 ° C to constant weight.
[0034] Modified carbon black: The amount added is 25% of the mass of the base rubber, i.e. 25 g. N330 carbon black with a particle size of 30 nm was dried in an oven at 110°C for 3 hours, added with a mixed solution of ethanol-water (volume ratio 4:1), ultrasonically dispersed at 200W for 40 minutes, added with ammonia water to adjust the pH to 10, added with tetraethyl orthosilicate at a mass ratio of 1:1, stirred at 50°C and 400 r / min for 4 hours, centrifuged, washed, dried at 70°C for 18 hours, and calcined at 500°C for 3 hours.
[0035] Plasticizer: acetyl tributyl citrate, the added amount is 10% of the base rubber mass, i.e. 10g.
[0036] Vulcanizing agent: dicumyl peroxide, the added amount is 2% of the base rubber mass, i.e. 2g.
[0037] Antioxidant: The mass ratio of antioxidant 4010NA and antioxidant RD is 1:1.5, and the total addition amount is 2% of the base rubber mass, i.e. 2g.
[0038] Other additives: The weight ratio of zinc oxide, stearic acid and accelerator is 4:1.5:1, and the total addition amount is 6% of the base rubber mass, i.e. 6g. The mass ratio of 2-mercaptobenzothiazole and N-cyclohexyl-2-benzothiazolesulfonamide in the accelerator is 1:1.7. Example 4
[0039] The rubber sealing strip prepared according to the method of Example 1, wherein Base rubber: The mass ratio of EPDM rubber and silicone rubber is 5:3, totaling 100g.
[0040] Modified montmorillonite: The addition amount is 12% of the base rubber mass, i.e. 12 g. 60 g of montmorillonite is added to 1 L of deionized water and ultrasonically treated for 25 min. 10 g of oleic acid is dissolved in 200 g of ethanol and reacted at 70 ° C for 4 h. Centrifuge, wash, and dry at 75 ° C to constant weight.
[0041] Modified carbon black: The addition amount is 26% of the base rubber mass, i.e. 26g. N550 carbon black with a particle size of 40nm was dried in an oven at 115℃ for 3.5h, added with a mixed solution of ethanol-water (volume ratio 4.5:1), ultrasonically dispersed at 250W for 50min, ammonia water was added dropwise to adjust the pH to 10.5, and tetraethyl orthosilicate was added dropwise at a mass ratio of 1.5:1, stirred at 55℃ and 500r / min for 5h, centrifuged, washed, dried at 75℃ for 20h, and calcined at 550℃ for 3.5h.
[0042] Plasticizer: Tributyl citrate and acetyl tributyl citrate are mixed in a mass ratio of 1:1, and the added amount is 11% of the mass of the base rubber, i.e. 11g.
[0043] Vulcanizing agent: Di-tert-butyl diisopropylbenzene peroxide and diisopropylbenzene peroxide are mixed in a mass ratio of 1:1, and the added amount is 2.2% of the mass of the base rubber, i.e. 2.2g.
[0044] Antioxidant: The mass ratio of antioxidant 4010NA and antioxidant RD is 1:2, and the total addition amount is 2.5% of the base rubber mass, i.e. 2.5g.
[0045] Other additives: The weight ratio of zinc oxide, stearic acid and accelerator is 4.5:1.8:1.5, and the total addition amount is 7% of the base rubber mass, i.e. 7g. The mass ratio of 2-mercaptobenzothiazole and N-cyclohexyl-2-benzothiazolesulfenamide in the accelerator is 1:1.8. Example 5
[0046] The rubber sealing strip prepared according to the method of Example 1, wherein Base rubber: The mass ratio of EPDM rubber and silicone rubber is 5:4, totaling 100g.
[0047] Modified montmorillonite: The addition amount is 15% of the base rubber mass, i.e. 15 g. 80 g of montmorillonite is added to 1 L of deionized water and ultrasonically treated for 30 min. 10 g of oleic acid is dissolved in 200 g of toluene and reacted at 80 ° C for 6 h. Centrifuge, wash, and dry at 80 ° C to constant weight.
[0048] Modified carbon black: The addition amount is 28% of the base rubber mass, i.e. 28g. N375 carbon black with a particle size of 50nm was dried in an oven at 120℃ for 4h, added with a mixed solution of ethanol-water (volume ratio 5:1), ultrasonically dispersed at 300W for 60min, ammonia water was added dropwise to adjust the pH to 11, ethyl orthosilicate was added dropwise at a mass ratio of 2:1, stirred at 60℃ and 600r / min for 6h, centrifuged, washed, dried at 80℃ for 24h, and calcined at 600℃ for 4h.
[0049] Plasticizer: tributyl citrate, the added amount is 12% of the base rubber mass, i.e. 12g.
[0050] Vulcanizing agent: dicumyl peroxide, the added amount is 2.5% of the base rubber mass, i.e. 2.5g.
[0051] Antioxidant: The mass ratio of antioxidant 4010NA and antioxidant RD is 1:1, and the total addition amount is 3% of the base rubber mass, i.e. 3g.
[0052] Other additives: The weight ratio of zinc oxide, stearic acid and accelerator is 5:2:2, and the total addition amount is 8% of the base rubber mass, i.e. 8g. The mass ratio of 2-mercaptobenzothiazole and N-cyclohexyl-2-benzothiazolesulfonamide in the accelerator is 1:2. Comparative Example 1
[0053] The modified montmorillonite and modified carbon black were removed, and only unmodified montmorillonite was added. The other parameters were consistent with those in Example 5. Comparative Example 2
[0054] The modified montmorillonite and modified carbon black were removed, and only unmodified carbon black was added. The other parameters were consistent with those in Example 5. Comparative Example 3
[0055] Except for the modified montmorillonite and modified carbon black, the other parameters are consistent with those in Example 5. Comparative Example 4
[0056] The modified carbon black was removed and the remaining parameters were consistent with those in Example 5. Comparative Example 5
[0057] The modified montmorillonite was removed and the remaining parameters were consistent with those in Example 5.
[0058] The performance of the rubber sealing strips in Examples 2-5 and Comparative Examples 1-5 was tested, and the data are shown in Table 1 below.
[0059] Table 1
[0060] It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.
Claims
1. A rubber sealing strip, characterized in that: The raw materials of the rubber sealing strip include basic rubber, modified montmorillonite, modified carbon black, plasticizer, vulcanizer, antioxidant and other additives; The preparation method of modified montmorillonite is: Montmorillonite is added into deionized water and ultrasonically treated for 15-30 minutes to obtain a montmorillonite suspension; Dissolve oleic acid in an organic solvent, stir evenly to make the oleic acid completely dissolved, and obtain an oleic acid solution; Add the montmorillonite suspension to the oleic acid solution while stirring. After the reaction is completed, centrifuge the product, wash it repeatedly with ethanol or deionized water for more than 3 times, and then dry the washed product at 60-80°C to constant weight to obtain modified montmorillonite. The preparation method of modified carbon black is: Add carbon black to an ethanol-water mixed solution, and disperse by ultrasonic at 100-300W for 30-60min to obtain a carbon black dispersion; Add ammonia solution to the carbon black dispersion, adjust the pH value to 9-11, and then continue to add tetraethyl orthosilicate. After the addition is completed, place the reaction system in a constant temperature water bath, and react at a temperature of 40-60°C and a stirring speed of 300-600r / min for 2-6h; After the reaction is completed, the reaction solution is centrifuged at a speed of 4000-6000 r / min for 10-20 min, the supernatant is discarded, and then the precipitate is washed alternately with anhydrous ethanol and deionized water for 3-5 times; The washed precipitate is placed in an oven at 60-80°C and dried for 12-24 hours until constant weight is reached; The dried sample is placed in a high temperature furnace and calcined at 400-600°C for 2-4 hours to obtain modified carbon black.
2. A rubber sealing strip according to claim 1, characterized in that: The base rubber is composed of EPDM rubber and silicone rubber in a mass ratio of 10:3-8.
3. A rubber sealing strip according to claim 1, characterized in that: The added amount of the modified montmorillonite is 8-15% of the mass of the basic rubber, and the added amount of the modified carbon black is 22-28% of the mass of the basic rubber.
4. A rubber sealing strip according to claim 1, characterized in that: The plasticizer is one of tributyl citrate and acetyl tributyl citrate or a mixture of the two, and the added amount is 8-12% of the mass of the base rubber.
5. A rubber sealing strip as claimed in claim 1, characterized in that: The vulcanizing agent is one of di-tert-butyl diisopropylbenzene peroxide and diisopropylbenzene peroxide or a mixture of the two, and the added amount is 1.5-2.5% of the mass of the base rubber.
6. A rubber sealing strip as claimed in claim 1, characterized in that: The antioxidant is compounded by antioxidant 4010NA and antioxidant RD in a mass ratio of 1:1-2, and the total addition amount is 1-3% of the mass of the base rubber.
7. A rubber sealing strip according to claim 1, characterized in that: Other additives include zinc oxide, stearic acid and accelerator in a weight ratio of 3-5:1-2:0.5-2, and the total addition amount is 5-8% of the mass of the base rubber. The accelerator is a mixture of 2-mercaptobenzothiazole and N-cyclohexyl-2-benzothiazole sulfenamide, and the mass ratio of 2-mercaptobenzothiazole and N-cyclohexyl-2-benzothiazole sulfenamide is 1:1.5-2.
8. A rubber sealing strip as claimed in claim 1, characterized in that: The ratio of montmorillonite to deionized water in the montmorillonite suspension is 30-80 g / L; The weight ratio of oleic acid to organic solvent is 1:10-20, and the organic solvent is one of ethanol or toluene; The reaction temperature of montmorillonite and oleic acid is 50-80°C, and the reaction time is 2-6h.
9. A rubber sealing strip as claimed in claim 1, characterized in that: The particle size of carbon black is 20-50nm; The carbon black was pretreated by drying in an oven at 100-120°C for 2-4h before being added to the ethanol-water mixed solution; The volume ratio of ethanol to water in the ethanol-water mixed solution is 3:1-5:1; The mass fraction of the ammonia solution is 25-28%wt; The mass ratio of ethyl orthosilicate to carbon black is 0.5:1-2:1, and the dropping speed of ethyl orthosilicate is 1-2 drops / second.
10. The method for preparing a rubber sealing strip according to any one of claims 1 to 9, characterized in that: The following steps are involved: Add the base rubber to the open mill, set the roller distance to 3-5mm, the roller temperature to 40-60℃ for plastication, and the time is 10-15min; Put modified montmorillonite, modified carbon black and grinding balls into a ball mill in a certain proportion, with a ball-to-material ratio of 5-10:1, set the speed of the ball mill to 200-500r / min, and the ball milling time to 4-10h. After the ball milling is completed, separate the grinding balls through a sieve and collect the blend; The plasticized base rubber is put into an internal mixer, the initial temperature of the internal mixer is set to 50-60°C, and then the blend of modified montmorillonite and modified carbon black, plasticizer, antioxidant and other additives are added in sequence, and mixed for 8-12 minutes, with the rotor speed of 40-60r / min to make the components fully mixed; Finally, add the vulcanizing agent and continue mixing for 3-5 minutes. Put the mixed rubber into the hopper of the extruder. The extruder temperature is controlled at 60-100℃ and the screw speed is 20-40r / min. The rubber is extruded into the required sealing strip shape through the extrusion die. The extruded sealing strip is vulcanized with hot air, the vulcanization temperature is controlled at 160-180℃, the vulcanization time is 10-20min, and the vulcanized sealing strip is cooled to room temperature through a cooling water tank, and the cooling water temperature is controlled at 10-20℃; The cooled sealing strip is cut to obtain a rubber sealing strip.
Citation Information
Patent Citations
Low-temperature-resistant salt-spray-resistant rubber sealing material and preparation method thereof
CN111004420A
Preparation method of nano SiO2-carbon black two-phase filler
CN111849217A
Ethylene-propylene-diene monomer composite rubber material and preparation method thereof
CN112321952A
Automobile sealing strip rubber material, preparation method and automobile sealing strip
CN119019803A
Organic-inorganic composite vulcanized nitrile rubber for sealing element and preparation method therefor
WO2015154492A1
Cited By
Heavy-duty anti-corrosion coating applied to outer wall of wind power generation tower drum and preparation method of heavy-duty anti-corrosion coating
CN120230456A
Carbon black composite intercalated styrene-butadiene rubber and preparation method thereof
CN120904550A
High and low temperature resistant rubber material for automobile turbocharging pipeline and preparation method of high and low temperature resistant rubber material
CN122404876A